A case study on integrated management of water losses in Antalya, Turkey. Issue 10 (16th September 2022) - Akdeniz, Tugba
Abstract: In this study, effects of the combination of meter replacement and active leakage control on real and apparent losses are investigated. Generally, water meter replacement campaigns, SCADA system operation, data analysis studies and physical leak detection activities are carried out by different units in water utilities. Within the scope of this study, the studies carried out by different units of the water utility were carried out in an integrated manner in the same period and the obtained data sets were analysed together. Thus, water losses, which were at the level of 52% in the pilot study area (PSA), were reduced to 35%. When the volumes of water supplied to the system before and after the study are compared, the volumes after the study were decreased. Also, water losses in the PSA have been reduced by 17%. HIGHLIGHTS: Reducing water losses is not only a revenue problem, it also results in wasting sources. Effects of integrated management techniques on water losses are investigated. The application in this study by different water utilities will contribute to the management of water losses in WDS. The importance of regular active leakage control studies has been proved. As a result of the study, water losses were reduced by 17%.